Modelling and experimental investigations on gasification of coarse sized coal char particle with steam. Issue 5 (October 2019) - Prabhakar, Ashok; Sadhukhan, Anup Kumar; Bhunia, Shyamal; Gupta, Parthapratim
Abstract: The steam gasification characteristics of coal char produced two sub-bituminous coals of different origin have been investigated through modelling and experiments. The gasification experiments are carried out in an Isothermal mass loss apparatus over the temperature range of 800–900 °C using a gas mixture of 65% steam and 35% N2 . A fully transient single particle gasification model, based on the random pore model, is developed incorporating reaction kinetics, heat and mass transport inside the porous char particle and the gas film. Stefan-Maxwell equation and Knudson diffusion are incorporated in the multi-component diffusion of species and pore diffusion. The model is validated with the experimental data of the present authors as well as that reported in the literature. The particle centre temperature is found to increase, then decrease and increase again to reach the reactor temperature finally, and the trend is more prominent for the larger particles. The pore opening phenomenon is more evident in SBC2 char, leading to a final char porosity of 0.65 vis-à-vis 0.52 in SBC1 and making it more reactive. Temporal evolution of contours of carbon conversion and concentration of other gaseous species like steam, H2 O, H2, CO and CO2 in the particle are computed to investigate the gasification process. A higher temperature is found to favour both the rate peak and the total production of H2 for both the chars. The total H2 production from SBC2 char is found to be 0.0189 mol and 0.0236 mol at 800 and 850 °C, while the same for SBC1 char is0.0232 mol and 0.0290 mol respectively. The reaction follows the shrinking core model at the outset, shifting to the shrinking reactive core model subsequently. Highlights: A fully transient model for steam gasification of coal char with multiple reactions is formulated.. The prominent effect of endothermic steam-gasification and Boudouard reactions, for higher particle size is identified. The yield of hydrogen is strongly affected both by the coal char type and reactor temperature. The reaction mechanism start with Shrinking Core Model and subsequently it shifts to Shrinking Reactive Core Model.